PROBLEMATIKA DAN JALAN TENGAH TERHADAP JUAL BELI BARANG ONLINE - Nisa, Hoirun (LP2M Institut Agama Islam Nurul Hakim, 2021)
The article tries to set off from reality that the online system is faulty. Including, first, buyers pay first before goods are brought in, this often leads to fraud. Second, the buyer cannot see the merchandise directly, so there is often a discrepancy between what is on the load and what is delivered. In this study, researchers will attempt to analyze the hadith's purchase of magical goods, and then retract them into the context of online trading. Using a descriptive method of analysis: researchers seek out hadiths that have a relevance to the buying and buying of psychic goods, look pro-opposing scholars at the theme and then take the middle course between the two. The results of this study that: first, the parties of the sellers of magical goods must explain in detail and specific terms regarding the items offered. In other words the seller must be honest, not only to explain the quality or excess of the goods, but to point out where the perceived deficiencies, defects or damage to the goods are offered. So the buyers understand the details of the surplus and lack of the goods. Second, while the seller may have explained in advance the surplus and lack of the goods, the parties should (still) give the chiyar rights to the buyer. Third, it is good to make payments after the goods are received.